Tutorial pembuatan media pembelajaran berbasis kuis oodlu - Sari, Arik Mustika (Educenter : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study can be used to determine the extent to which the development of the Oodlu quiz media on the eye sense material for 4th grade elementary school students. To determine the feasibility of Oodlu learning media on the sensory material of 4th grade elementary school students. primary school. In this study, not only are my goals described, but there are also benefits that underlie this research. This research is expected to be especially useful for writers and readers both theoretically and practically. This quiz media development research has gone through a validation process. based on validation that has been tested by experts, the research developed has results that are quite feasible to use during learning and have been declared valid by experts. This research is about the development of oodlu quiz learning media. Researchers raised quiz-based learning media to refresh the previously boring classroom atmosphere to become more fun. In the development of this OODLU quiz media, researchers used the 4D development stages or processes, namely Define (define), Design (design), Develop (development), Disseminate (Deployment). Definition of Stage (Definition) The definition related to development needs is the initial stage in the 4D model. At the stage of needs analysis, it is necessary to collect information data about the media to be developed. The last stage is dissemination, so that the media that has been developed will be distributed to students and teachers.